BOLOGNA ACCORDS IMPLEMENTATION AS A FACTOR OF QUALITY ASSURANCE OF EUROPEAN HIGHER EDUCATION (EXPERIENCE OF THE CZECH UNIVERSITY OF LIFE SCIENCES PRAGUE) - V. Cerny; V. А. Glikhikh (Дискурс, 2016)
The article presents the experience of the Czech University of Life Sciences Prague in implementation of the Bologna Accords in European Higher Education. Positive results are analyzed and some current problems are outlined.